METASTATIC RADIOIODINE AVID STRUMA OVARII ASSOCIATED WITH PSEUDO-MEIGS’ SYNDROME - Riaz, Saima; Bashir, Humayun; Hassan, Aamna; Syed, Aamir Ali; Hussain, Mudassar; Imtiaz, Saba (Journal of Ayub Medical College Abbottabad, 2015)
We report a case of 21 years old lady who presented with ascites, left adnexal mass and elevated CA-125. With suspicion of ovarian malignancy, she underwent left salpingo-oophorectomy with omental biopsy. Histopathology revealed: ’˜follicular variant of papillary thyroid carcinoma arising in struma ovarii’ with metastatic papillary thyroid carcinoma in omental and peritoneal nodules. Patient underwent total thyroidectomy followed by radioactive iodine therapy for metastatic omental and peritoneal disease. Post-therapy whole body scan, revealed extensive I-131 avid disease metastatic disease involving the chest, abdomen, pelvis and the musculoskeletal system. Patient was treated with multiple doses of high dose radioactive iodine. She became symptom free on supra-physiologic doses of oral thyroxin however her high thyroglobulin levels and residual radioiodine avid metastatic disease required further treatment. In literature a few cases of struma ovarii have been reported with elevated CA-125 and associated pseudo-Meigs’ syndrome. The treatment for this rare disease is still not standardized and poses a therapeutic challenge. Our case emphasizes the need for a multidisciplinary approach for managing struma ovarii.